(untitled) (Світ фінансів, 2017)
Дем’янишин В. Г. Податковий механізм формування доходів бюджету: концептуальні засади теорії та напрями модернізації. Розкрито сутність податкового механізму та підходи до його трактування у широкому та вузькому значенні. Зазначено, що у структурі податкового механізму використовуються взаємозв’язані між собою елементи, зокрема, підсистеми, форми, методи, важелі, інструменти, стимули та санкції. Аргументовано, що складовими податкового механізму залежно від завдань, набору інструментів, наявності суб’єктів та способу дій є дві підсистеми: механізм справляння податків платниками та механізм контролю забезпечення сплати податків. Розкрито зміст зазначених підсистем. Проаналізовано роль податків у розподілі і перерозподілі ВВП. Рекомендовано систему оподаткування формувати на науковій основі, розробивши її стратегію, яка включала б визначення оптимальних пропорцій розподілу ВВП за допомогою податків, співвідношення між прямим і непрямим оподаткуванням, суб’єктами та об’єктами оподаткування, загальнодержавними та місцевими податками і зборами. Запропоновано напрями модернізації податкового механізму формування доходів бюджету. Демьянишин В. Г. Налоговый механизм формирования доходов бюджета: концептуальные основы теории и направления модернизации. Раскрыта сущность налогового механизма и подходы к его трактовке в широком и узком смысле. Отмечено, что в структуре налогового механизма используются взаимосвязанные между собой элементы, в частности, подсистемы, формы, методы, рычаги, инструменты, стимулы и санкции. Аргументировано, что составляющими налогового механизма в зависимости от задач, набора инструментов, наличия субъектов и способа действий существуют две подсистемы: механизм взимания налогов плательщиками и механизм контроля обеспечения уплаты налогов. Раскрыто содержание указанных подсистем. Проанализирована роль налогов в распределении и перераспределении ВВП. Ре- комендовано систему налогообложения формировать на научной основе, разработав ее стратегию, которая включала бы определение оптимальных пропорций распре- деления ВВП с помощью налогов, соотношение между прямым и косвенным налогообложением, субъектами и объектами налогообложения, общегосударственными и местными налогами и сборами. Предложены направления модернизации налогового механизма формирования доходов бюджета. Demianyshyn V. Tax mechanism of budget revenues formation: the conceptual foundations of theory and modernization trends. Introduction. In Ukraine there is no fundamental theoretical and practical research of tax mechanism. The mechanism’s great importance for both financial theory and practice together with the existence of deficiencies and problems determine the relevance of research topic. Purpose. Evaluation of theoretical and practical principles of tax mechanism, developing recommendations for its improvement. Results. The research shows the essence of tax mechanism and approaches to its treatment in the broad and narrow sense, particularly as a set of techniques and methods by which the government using taxes affects the socio-economic development, and as a mechanism to ensure the functioning of the tax system. It is noted that the structure of the tax mechanism has separate components, which are interconnected with each other, particularly subsystems, forms, methods, instruments, tools, incentives and sanctions. The work gives reasons for the assumption that the tax mechanism components, depending on the tasks set, instruments available, subjects and modus operandi, fall into two subsystems: the mechanism of tax collection by taxpayers and control mechanism to ensure the payment of taxes; the work also clarifies the nature of these mechanisms. The role of taxes in the distribution and redistribution of GDP is analyzed. It is concluded that the increase in the share of tax revenues to GDP and budget revenues indicates the state policy aimed at strengthening the centralization of GDP. It is recommended to form taxation system on a scientific basis by developed its strategy that would include determining the optimal proportions of distribution of GDP through taxes and the ratio between direct and indirect taxation, subjects and objects of taxation, state and local taxes and duties. The author offers modernization ways of tax mechanism of budget revenues formation, including: reform of the tax system on the basis of economic efficiency, social justice and political responsibility; formation of a new institutional taxation environment; changes in tax structure and their distribution between the links of the budget system; rationalization of tax incentives; adaptation of tax legislation to the EU; improving the efficiency of tax policies, improve the management of the tax system and mechanism of functioning of individual taxes; optimization of the tax base, simplifying the tax assessment and collection. Conclusion. Modernization of the tax mechanism is recommended to be implemented by determining tax policy strategy, optimizing distribution and redistribution of GDP through taxes, reforming the tax system, simplifying and structuring the system of taxation, and adapting tax legislation to the EU standards.